PENGARUH CASH RATIO (CR) DAN DEBT TO ASSET RATIO (DAR) TERHADAP RETURN ON ASSET (STUDI KASUS PT CITILINK INDONESIA TAHUN 2017-2021) - Muhammad Distian Andi Hermawan (Program Studi Manajemen dan Magister Manajemen, Fakultas Ekonomika dan Bisnis, Universitas Katolik Widya Mandira, 2023)
In this study has the aim to see the influence of the financial system on the ratio of debt and profit together and also individually. The data used in this study uses secondary data obtained on the Indonesia Stock Exchange website with a time of 2017 to 2021. The analysis tool used in this study used SPSS software version 24. The results of this study show that the variables of financial literacy (X1) and financial behavior (X2) do not have a positive and significant influence on investment decisions (Y) both in testing together and individually